1
$\begingroup$

I'm trying to decompose the MSE into the bias and variance terms and have done the following: $$MSE = \frac{1}{n}\sum_{i=1}^{n}(y_i - \hat{y_i})^2$$

$$E(MSE) = E\left[\frac{1}{n}\sum_{i=1}^{n} (y_i - \hat{y_i})^2\right]$$

$$ = \frac{1}{n}\sum_{i=1}^{n}E[(y_i - \hat{y_i})^2] $$ $$ = \frac{1}{n}\sum_{i=1}^{n}E[y_i^2 - 2\hat{y_i}y_i + \hat{y_i}^2] $$ $$ = \frac{1}{n}\sum_{i=1}^{n}\{Var[y_i] + Var[\hat{y_i}] + E[y_i]^2 + E[\hat{y_i}]^2 - 2E[\hat{y_i}y_i]\}$$ $$ = \frac{1}{n}\sum_{i=1}^{n}\{\sigma^2 + Var[\hat{y_i}] + E[y_i]^2 + E[\hat{y_i}]^2 - 2E[\hat{y_i}y_i]\}$$

However, I am not sure how to factor the last three terms into the bias$^2$ term. Would it be correct to assume $y_i$ and $\hat{y_i}$ are independent and hence write $E[y_i\hat{y_i}]=E[y_i]E[\hat{y_i}]$?

$\endgroup$

1 Answer 1

1
$\begingroup$

The random part is $\hat{y}_i$, \begin{align} E[y_i]^2 + E[\hat{y}_i]^2-2E[\hat{y}_iy_i] &= y_i^2+E[\hat{y}_i]^2-2y_iE[\hat{y}_i] \\ &=(y_i-E[\hat{y}_i])^2 \end{align}

$\endgroup$
0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.